2022-RA-1533-ESGO Role of fertility sparing surgery in patients with borderline ovarian tumors - Westermann, Timo; Heitz, Florian; Ataseven, Beyhan; Pauly, Nina; Moubarak, Malak; Strojna, Aleksandra; Kaiser, Sabrina; Nicole, Concin; Welz, Julia; Vrentas, Vasileios; Dagres, Timoleon; Imterat, Majdi; et al. (International journal of gynecological cancer, 2022)
Introduction/BackgroundBorderline ovarian tumors (BOT) are considered rare tumors of the ovary and often occur in young patients, which is why fertility-sparing surgery (FSS) is of great importance.MethodologyPatients treated with a BOT between 1999 and 2022 in our gynecologic oncology center were included in this analysis. In all cases, an external pathological review was performed.ResultsAmong 469 patients, 365 (77.8%) were identified with FIGO stage I and 104 (22.2%) with FIGO stage ≥II. 138 patients (29.4%) received FSS. Among those patients treated with complete surgical staging, 5/331 (1.5%) relapses and 4/331 (1.2%) malignant transformations were observed, with a recurrence rate of 0/258 (0%) in FIGO I and 5/73 (6.8%) in FIGO II-IV. FSS showed 17/138 (12.3%) recurrences and 1/138 (0.7%) malignant transformation, with a recurrence rate in FIGO I of 6/107 (5.6%) and in FIGO II-IV of 11/31 (35.5%). In the multivariate analysis, FIGO stages III-IV (HR = 22.7; 95% CI: 7.4–69; p <0.001) and FSS (HR = 18.2; 95% CI: 4.8–69; p <0.001) were identified as significant risk factors for recurrence. 35 patients were treated with a recurrence of a BOT. FSS was repeated in 11 (36.7%) patients. After FSS, the recurrence rate was 1/11 (9%). After complete surgical staging, 3/24 (12.5%) patients experienced a recurrence.ConclusionPatients with BOT who receive a quality assured treatment have a very low risk of a malignant transformation. After individual consideration, FSS is safe in BOT in early FIGO stages. Patients should be counseled about a higher risk of recurrence in cases of FSS, especially in higher FIGO stages. In selected cases, FSS can also be reconsidered in the recurrence situation.